Evaluation of chitinase production ability to antagonize Pyricularia Oryzae of bacteria and actinomycete strains isolated from rice root soil in Kien Giang Province - Đinh Anh Hòa; Trần Thị Phấn; Trần Thùy Trang; Nguyễn Thị Ánh Nguyệt; Nguyễn Thị Thùy Dương; Nguyễn Hải An; Lê Thị Mai Châm (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
The fungus Pyricularia oryzae is one of the agents causing rice blast disease. The mechanism of the infection is directing penetration through the plasma membrane, secreting cytotoxins, and forming infectious cells specialized for causing disease in rice plants in some species (Muni & Nadarajah, 2014). Therefore, biological products containing microorganisms that can antagonize fungal pathogens and are environmentally friendly, are promising measure to control this disease. Among the beneficial microorganisms, bacteria and rhizosphere actinomycetes are known as potential antagonistic groups in disease prevention caused by fungi. This study screened 11 actinomycetes and 10 bacteria with high chitinase activity from 09 rice rhizosphere soil samples in Kien Giang province. Among them, strains B.KG4.1 and S.KG1.1 have strong potential to inhibit Pyricularia oryzae fungus by co-culture method with antagonistic effectiveness reaching 90.9% and 87.41% after 15 days, respectively. Antagonistic activity to fungal pathogens of bacterial strains was positively correlated with their ability to secrete extracellular chitinase. Based on the morphological characteristics and 16S-rRNA gene sequencing, strain S.KG1.1 was identified as Streptomyces carpinensis and strain B.KG4.1 belongs to the Bacillus amyloliquefaciens group. With these characteristics, Bacillus amyloliquefaciens B.KG4.1 and Streptomyces carpinensis S.KG1.1 have the potential to be exploited in the production of biological products to control the fungus Pyricularia oryzae causing rice blast disease.